'Factual causation' and 'scope of liability': What's the difference?. Issue 2 (March 2014) - Hamer, David
<x xml:space="preserve">Abstract</x> According to a dominant view, for the negligent defendant to be held liable for the plaintiff's harm the plaintiff must establish first, that the breach was the 'factual cause' of the harm, and second, that the harm is within the 'scope of liability'. On this view, factual causation is purely factual, while scope of liability is normative and non‐causal. This article accepts the basic two‐step approach, but argues that the distinction is overstated. A close analysis of the principles shows that factual causation may require value judgment, and that scope of liability often involves an assessment of the strength and nature of the causal connection between breach and harm.